Appendectomy and the subsequent risk of cancer: A prospective population-based cohort study with long follow-up. (April 2022) - van den Boom, A.L.; Lavrijssen, B.D.A.; Fest, J.; Ikram, M.A.; Stricker, B.H.; van Eijck, C.H.J.; Ruiter, R.
Abstract: Background: The appendix, an organ of immunological and microbiological importance, could be involved in the pathogenesis of cancers, but results are inconclusive. Our objective was to assess the association between appendectomy and the subsequent risk of cancer. Methods: Data were obtained from the Rotterdam Study; a long-term prospective population-based study of individuals aged 55 years and older, of which the first cohort started in 1990 and included 7983 participants. Information on appendectomy was obtained through either medical interview at baseline or linkage with the national automated pathology center (PALGA). Cancer cases were pathology based. End of follow-up was January 1st, 2015. The association between appendectomy and risk of cancer was assessed using Cox proportional hazard models, adjusted for known confounders. Results: Of 7135 included participants, 1373 (19.2%) had undergone an appendectomy and 1632 individuals developed cancer. After adjustment for age, sex, socioeconomic status, BMI, smoking, prevalent diabetes mellitus and alcohol intake, a history of appendectomy was associated with a significantly lower risk of cancer [hazard ratio (HR) 0.86, 95% confidence interval (CI) 0.75-0.98]. Subgroup analyses showed similar results for gastrointestinal cancer (HR 0.75, 95% CI 0.56-0.99), in particular colon cancer (HR 0.65, 95% 0.43-0.97), and cancer of the female reproductive organs (HR 0.35, 95% CI 0.15-0.80). Conclusion: Participants who underwent an appendectomy had a reduced risk of cancer in general after adjustment for potential confounders. Therefore, these results contradict earlier studies suggestive of an increased risk. Further research is necessary to replicate these results and reveal its underlying mechanism. Highlights: History of appendectomy is not associated with an increased risk of developing cancer. Risk of developing gastro-intestinal cancer was decreased after appendectomy. Similar decreased risks were found in colorectal and female reproductive organs cancer. This is the first prospective study on this topic to adjust for potential confounders other than age and sex.